Investigation of Halogen Bonding Interactions Through Solid-State Nuclear Magnetic Resonance and Nuclear Quadrupole Resonance - Morin, Vincent (Université d'Ottawa / University of Ottawa, 2021)
Electrostatic interactions such as halogen bonding and pnictogen bonding interactions have gained a lot of interest in the field of crystal engineering and pharmaceutical science. In the first part of this thesis, we expand our knowledge on anion coordinated halogen bonded cocrystals by looking at a series of cocrystals made from 3-iodoethynyl pyridine and 3-iodoethynylbenzoic acid. We utilize the power of mechanochemistry to create the new cocrystals made with phosphonium salts and use multinuclear solid-state nuclear magnetic resonance spectroscopy and X-ray diffraction and characterize them. We found that mechanochemistry is a fast and powerful tool to explore and synthesize new halogen bonded cocrystals and ³¹P solid-state NMR is a rapid way to identify the formation of a cocrystal. In the second part, we look at the versatility of the pnictogen atom, specifically antimony, as a pnictogen bond donor and a halogen bond acceptor. We evaluate these electrostatic interactions with nuclear quadrupolar resonance and found that nuclear quadrupole resonance is a strong spectroscopy tool to probe these types of electrostatic interactions.
Keywords: Solid-state nuclear magnetic resonance; Nuclear quadrupole resonance; Electrostatic interactions; Pnictogen bonding; Halogen bonding; X-ray diffraction